Bioefficacy of the triterpenoid friedelin against Helicoverpa armigera (Hub.) and Spodoptera litura (Fab.) (Lepidoptera: Noctuidae). Issue 12 (26th February 2014) - Baskar, Kathirvelu; Duraipandiyan, Veeramuthu; Ignacimuthu, Savarimuthu
Abstract BACKGROUND The triterpenoid friedelin isolated from hexane extract of Azima tetracantha leaves was evaluated for its antifeedant, larvicidal and pupicidal activities against Helicoverpa armigera and Spodoptera litura at 125, 250, 500 and 1000 ppm concentration. RESULTS Friedelin exhibited antifeedant (84.57 and 75.28%), larvicidal (72.88 and 66%) and pupicidal (76.18 and 66.66%) activities against H. armigera and S. litura respectively. The homogeneity of variances (Levene statistic) showed significant deviation for the antifeedant, larvicidal and pupicidal activities of friedelin against H. armigera and S. litura. It exhibited LC50 values of 130.47 and 226.41 ppm for antifeedant and 509.56 and 607.99 ppm for larvicidal activities against H. armigera and S. litura respectively. In linear regression analysis, significant and high correlation was noted between concentration and antifeedant activity with R2 = 0.84 and 0.79 and between concentration and larvicidal activity with R2 = 0.81 and 0.76 against H. armigera and S. litura respectively. CONCLUSION Regression between antifeedant and larvicidal activities also showed significant activity (P = 0.00) with R2 = 0.79 for H. armigera and R2 = 0.70 for S. litura. Friedelin showed good activity against both the pests. Friedelin did not show any toxicity against freshwater fish Cyprinus carpio at 100 mg L−1. Friedelin could be used to prepare a botanical formulation to control the agricultural pests. © 2014 Society of Chemical Industry